Regulation of the Fear Network by Mediators of Stress: Norepinephrine Alters the Balance between Cortical and Subcortical Afferent Excitation of the Lateral Amygdala - Johnson, Luke R.; Hou, Mian; Prager, Eric M.; LeDoux, Joseph (Frontiers in Behavioral Neuroscience, 2011)
Pavlovian auditory fear conditioning crucially involves the integration of information about and acoustic conditioned stimulus (CS) and an aversive unconditioned stimulus (US) in the lateral nucleus of the amygdala (LA). The auditory CS reaches the LA subcortically via a direct connection from the auditory thalamus and also from the auditory association cortex itself. How neural modulators, especially those activated during stress, such as norepinephrine (NE), regulate synaptic transmission and plasticity in this network is poorly understood. Here we show that NE inhibits synaptic transmission in both the subcortical and cortical input pathway but that sensory processing is biased towards the subcortical pathway. In addition binding of NE to β-adrenergic receptors further dissociates sensory processing in the LA. These findings suggest a network mechanism that shifts sensory balance towards the faster but more primitive subcortical input.